Bicadinanes and related compounds as maturity indicators for oils and sediments - Sosrowidjojo, Imam B.; Murray, Andrew P.; Alexander, Robert; Kagi, Robert I.; Summons, Roger E. (Organic geochemistry, 1996)
Biomarker maturity indices have proven useful in petroleum exploration to assess the thermal maturity of oils and sediments. However, their application to deltaic petroleum systems is often hindered by source and diagenetic interferences. Recently, we have described several new maturity indices based on the catagenetic products of the plant biopolymer polycadinene. These indices should be largely immune to biochemical effects during diagenesis, since little microbial activity will remain at temperatures sufficient to dissociate the polymer. Here we report changes in five polycadinene-related maturity indices through a marine-fluvio-deltaic depositional sequence in the South Sumatra Basin, Indonesia. The results are compared with the maturity required for oil generation as estimated by kinetic modelling and with conventional maturity indicators such as sterane epimerisation and the methyl phenanthrene index. The data confirm that the polycadinene indices are less subject to source and diagenetic interferences than those based on the sterane and aromatic hydrocarbon distributions. Values for several of the indices have also been measured for 17 Tertiary oils from Southeast Asia, Papua New Guinea, New Zealand and Australia. Contrary to an earlier report, the bicadinane maturity indicator (BMI-1) continues to change into the oil window and hence may be useful in ranking the relative maturity of oils as well as sediments. The BMI-1 values for two oils having unusually low sterane maturities are normal, leading us to question whether the low sterane maturity of many Tertiary-age oils is due to their source rocks having been heated more rapidly than those of older oils.